Competency Level in Information and Communications Technology (ICT) of Teachers: Basis for a Technological, Pedagogical and Content Knowledge (TPACK) readiness training program - Ibarrientos, Jessica N. (Indonesian Journal of Teaching in Science, 2024)
The study is aimed at determining the level of competence of information and communications technology (ICT) secondary teachers in the City Division of Ligao. Specifically, it is done to answer the following questions: (1) What is the demographic profile of the respondents in terms of age, sex, educational attainment, length of service, number of training attended related to ICT, and other qualifications? (2) What is the competency level of Technology and Livelihood Education (TLE)-ICT teachers in the four competency domains: technology operations and concepts, social and ethical, pedagogical, and professional domains? (3) Is there a significant relationship between the demographic profile and the competency level of the ICT teachers along the four domains? (4) What training design can be proposed based on the findings of the study? A descriptive, evaluative, and survey method of research was utilized in this study. The instrument used in this study was a survey questionnaire adapted from the National ICT Competency Standard Framework (NICS). The gathered data were interpreted and analyzed using different statistical tools such as frequency distribution, percentage technique, mean, weighted mean, Likert scale, and chi-square test for independence.